UK institutions for tax governance: reviewing tax settlements - Freedman, J (Sweet and Maxwell, 2016)
Reflects on criticisms of HMRC's 2016 settlement with Google, and whether, despite creating a Tax Assurance Commissioner (TAC) to ensure such settlements are appropriate, further reforms are needed to improve transparency and address public concerns. Assesses the TAC's role and whether the Public Accounts Committee needs extra powers in such situations. Suggests how creating an expert unit of the National Audit Office may provide a solution.